Out-of-field scattering from the Integral Quality Monitor® in megavolt photon beams. (February 2021) - Ade, Nicholas; du Plessis, F.C.P.
Abstract: Purpose: To investigate out-of-field scattered doses from the Integral Quality Monitor (IQM) transmission detector in megavoltage photon beams. Materials and methods: We measured out-of-field point doses for 20 × 20 cm 2 6–15 MV photon beams using 10 × 2 cm 2 Gafchromic EBT3 film strips placed across the surfaces of 5-cm thick water-equivalent RW3 slabs. The films were placed at 10 cm intervals from the central axis (CAX) of each beam, up to 1.0 m away on opposite sides of the CAX. The measurements were conducted at 80 cm and 100 cm source-to-surface distances (SSD) without the IQM, and were repeated with the IQM in the paths of the beams. Measurements were also performed at 90 cm SSD for 20 × 20 and 30 × 30 cm 2 15 MV fields. Surface dose profiles were then constructed from the measurements for each beam setup with and without the IQM to examine the differences in scattered dose off-axis. The dose profile for each beam setup was normalised to dose maximum measured on the CAX. Results: Overall, surface dose profiles acquired with the IQM in the paths of the beams were higher than the corresponding profiles without the IQM. The out-of-field dose increased with increase in photon energy, field size, and shorter SSDs, and decreased with off-axis distance. At 80 cm SSD for the 20 × 20 cm 2 field, the IQM-induced surface dose ranged from −0.6% ÷ 1.9%, −0.3% ÷ 3.0%, and 0.3% ÷ 6.8% for 6, 10, and 15 MV beams, respectively. Conclusion: The higher surface dose profiles measured with the IQM attached to the linac compared to the profiles without the IQM indicates that the device is acting as an additional source of scattered radiation. Highlights: We studied out-of-field scatter from the IQM transmission detector using EBT3 film. We used 20 × 20 cm 2 and 30 × 30 cm 2 6 ̶ 15 MV photon beams and 80–100 cm SSD. Out-of-field surface dose increased with photon energy and field size. In addition, the out-of-field surface dose increased with decreasing SSD. For the beam setups, the IQM-induced surface dose ranged from −0.6% to 6.8%.